Back Cover: Human Urine‐Fueled Light‐Driven NADH Regeneration for Redox Biocatalysis (ChemSusChem 13/2016). Issue 13 (30th June 2016) - Choi, Woo Seok; Lee, Sahng Ha; Ko, Jong Wan; Park, Chan Beum
Abstract : The Back Cover picture shows a urine‐fueled, photoelectrochemical platform for visible light‐driven redox biocatalysis, where the oxidation of urea in human urine by Ni catalyst reduces the biological nicotinamide cofactors that are required for biocatalyzed redox conversions. The variety of nicotinamide cofactor‐dependent enzymes in nature provides a generality in the application of the urine‐fueled photobiocatalytic system. The present study, a first example of coupling of urea oxidation with biocatalysis based on the photoelectrochemical platform, should provide a new horizon towards both wastewater treatment and light‐driven biocatalysis. More details can be found in the Communication by Choi et al. onpage 1559 in Issue 13, 2016 (DOI:10.1002/cssc.201600330 ).